Candida albicans: Virulence factors, pathogenesis, and ways to diagnose and control its infection (Research, Society and Development, 2024)
The objective of this study was to provide a review on Candida albicans, focusing on its main virulence factors, pathogenesis, and methods of diagnosis and control of infections caused by this microorganism, known as candidiasis. Its main virulence factors are adhesion, polymorphism and dimorphism, which aid in tissue invasion, phenotypic variability, tolerance to toxins, and the presence of enzymes such as proteases and phospholipases. These factors confer the fungus with the ability to colonize, establish itself, and consequently, cause infections. C. albicans can proliferate on the skin and mucous membranes of the oropharyngeal cavity, gastrointestinal tract, and vaginal tract. The result of this colonization is the formation of white plaques or nodules with erythematous borders in the infected area. Additionally, it may cause pain and burning or be asymptomatic. The diagnosis of candidiasis is based on the symptoms presented by the host. Cultures, histopathological examinations, blood cultures, and serum beta-glucan tests can also be used. The treatment of candidiasis is carried out with antifungals such as nystatin, clotrimazole, fluconazole, itraconazole, and amphotericin B. However, research on medicinal plant products has been conducted to provide an integrative and complementary approach to controlling this pathogen. Thymus vulgaris L. is a good example of this. It is a plant with various phytochemicals and recognized biological activities, including antifungal effects. Thus, this study demonstrated some morphological and pathological characteristics of C. albicans. It was also possible to understand how candidiasis manifests, and how it can be diagnosed and treated both conventionally and integratively.